YouTube as a source of information on Merkel cell carcinoma - Abdullah Evren Yetişir (Galenos Publishing House, 2023)
Background and Design: To evaluate the content and reliability of Merkel cell carcinoma videos on YouTube, the most frequently used videosharing platform to access information. Materials and Methods: In this descriptive study, videos about Merkel cell carcinoma were searched on www.youtube.com using the term 'Merkel cell carcinoma', and 100 videos were analyzed using the Global Quality scale (GQS) and modified DISCERN tool. Results: The majority of the videos were related to treatment (72%), diagnosis (36%), and pathogenesis (19%). 81% of the videos were rated as useful and 19% as misleading. The GQS and DISCERN scores of the useful videos were statistically significantly higher than those of the misleading videos. Conclusion: The importance of YouTube, which contains both useful and misleading videos about health for public health, is increasing. Since Merkel cell carcinoma is a rare cancer, we found that the majority of the videos on this subject were uploaded by experts, and their rate of usefulness was high. In the selection of videos on health-related topics, the videos posted by experts (such as medical journals, doctors, and universities) should be prioritized, and YouTube should not be the only source of information since it has no supervisory mechanism.